Agricultural microcredit for tenant farmers: Evidence from a field experiment in Bangladesh - Hossain, Marup; Malek, Mohammad Abdul; Hossain, Md. Amzad; Reza, Md. Hasib; Ahmed, Md. Shakil (Wiley Online Library, 2022)
This article was published in The American Journal of Agricultural Economics [©2018 Published by the Agricultural and Applied Economics Association, Inc.] and the definite version is available at: https://doi.org/10.1093/ajae/aay070 The Article's website is at: https://onlinelibrary.wiley.com/doi/abs/10.1093/ajae/aay070